A National Study on Nurses’ Exposure to Occupational Violence in Lebanon: Prevalence, Consequences and Associated Factors - Alameddine, Mohamad (PLoS One, 2015)
BACKGROUND: Healthcare institutions have commonly reported exposure of employees, particularly nurses, to high levels of occupational violence. Despite such evidence in the Middle East Region, there is a dearth of national studies that have systematically investigated this phenomenon. This study investigates the prevalence, characteristics, consequences and factors associated with nurses’ exposure to occupational violence in Lebanon. METHODS: A cross-sectional design was utilized to survey a nationally representative sample of 915 nurses registered with the Order of Nurses in Lebanon. Stratified random sampling by governorate was utilized. Individually-mailed questionnaires collected information on exposure to violence, degree of burnout and demographic/professional background. The main outcome variables were exposure to verbal abuse (never, 1–3, 4–9 and 10+ times) and physical violence (never, ever) over the past 12-months. Descriptive statistics were used to estimate prevalence of violence. Multivariable, binomial and multinomial regression models were carried out to investigate the correlates of exposure to verbal abuse and physical violence, respectively. RESULTS: Response rate was 64.8%. Over the last year, prevalence of nurses’ exposure to verbal abuse was 62%, (CI: 58–65%) and physical violence was 10%, (CI: 8–13%). Among respondents, 31.7% of nurses indicated likelihood to quit their jobs and 22.3% were undetermined. Furthermore, 54.1% reported high levels of emotional exhaustion and 28.8% reported high levels of depersonalization. Compared to nurses with no exposure to verbal abuse, nurses reporting high exposure had high levels of emotional exhaustion (OR:6.4; CI:1.76–23.32), depersonalization (OR:6.8; CI: 3–15) and intention to quit job (OR:3.9; CI: 1.8–8.3). They further reported absence of anti-violence policies at their institutions (OR: 3; CI: 1.5–6.3). Nurses that were ever exposed to physical violence were more likely to be males (OR: 2.2; CI: 1.1–4.3), working day and night shifts (OR: 2.8; CI: 1.4–5.5) and subject to ten or more incidents of verbal abuse per year (OR: 46.7; CI: 10.1–214). CONCLUSIONS: An alarming two-thirds of respondents reported exposure to verbal abuse which was found to be a significant predictor of the three subscales of burnout, intention to quit and exposure to physical violence. The prevalence of exposure to physical violence is disconcerting due to its severe consequences. Policy and decision-makers are urged to use study findings for policy and practice interventions to create safe work environments conducive to nurses’ productivity and retention.